Correction: Recent advances in understanding of the mechanism and control of Li2O2 formation in aprotic Li–O2 batteries. (25th September 2017) - Lyu, Zhiyang; Zhou, Yin; Dai, Wenrui; Cui, Xinhang; Lai, Min; Wang, Li; Huo, Fengwei; Huang, Wei; Hu, Zheng; Chen, Wei
Abstract : Correction for 'Recent advances in understanding of the mechanism and control of Li2 O2 formation in aprotic Li–O2 batteries' by Zhiyang Lyu et al., Chem. Soc. Rev., 2017, DOI: 10.1039/c7cs00255f.